Observer-based fast nonlinear MPC for multi-DOF maglev positioning system: Theory and experiment - Zhang, Kaiyang; Xu, Fengqiu; Xu, Xianze (Control engineering practice, 2021)
This paper presents an observer-based fast nonlinear model predictive control (NMPC) scheme for translation control of magnetically levitated (maglev) positioning system subject to input saturation. The motivation lies in the improvement of transient characteristics and control performance for positioning systems. The nonlinear dynamical translation model of the maglev positioning system is derived that does not affect the rotation dynamics with special current conditions. The disturbance estimation, obtained by nonlinear disturbance observer, is introduced in the state receding prediction to compensate the errors caused by disturbances and uncertainties. To reduce the computational burden, the stability of the proposed NMPC is established without using any stability-related terminal costs or constraints, and only the short prediction horizon is required for real-time feasibility. The online optimization algorithm underlying the NMPC scheme takes the process constraints into account, and solves the optimal control problem using a parallel structure at each iteration. Comparative experiments are carried out on the positioner to validate the proposed controller has the outperformance in transient/steady-state trajectory tracking, frequency characteristics and robustness against disturbances. The proposed scheme also provides a guidance for the application of NMPC in industrial mechatronic system with fast dynamics. •Observer-based fast nonlinear MPC design is developed for maglev positioner.•Reasonable prediction horizon is analyzed to guarantee the stability of NMPC.•Disturbance effects are compensated by disturbance observer for offset-free tracking.•Real-time implementation of NMPC is based on a parallel Newton-type method.